AN INVENTORY OF THE BUTTERFLIES OF MANIPUR, INDIA (INSECTA: LEPIDOPTERA) - Irungbam, Jatishwor Singh; Meitei, Laishram Ricky; Huidrom, Harmenn; Soibam, Baleshwor Singh; Ngangom, Aomao; Ngangom, Bendang; Meitei, Ronald; Fric, Zdenek Faltynek (Zootaxa, 2020)
The butterfly fauna of Manipur is poorly known, and a few sporadic studies were carried out decades ago. In this study, butterflies were photographed and/or collected in 80 localities including revisiting of 12 historical localities in the hills and valleys from Manipur state, India. Butterflies were regularly sampled between 2010 and 2019. In the present checklist, we have included both previously published and recently recorded species: 798 species belong to six families; Papilionidae (52 sp.), Pieridae (39 sp.), Riodinidae (17 sp.), Lycaenidae (225 sp.), Nymphalidae (270 sp.), and Hesperiidae (195 sp.). Eight species were rediscovered during the study; Byasa latreillei kabrua, Papilio machaon suroia, Lamproptera meges indistincta, Bhutanitis lidderdalii lidderdalii, Lethe kangjupkula, Una usta usta, Arhopala hellenore hellenore and Celaenorrhinus munda maculicornis. Thirty–two species were new records to Manipur; Papilio agestor agestor, Lamproptera curius curius, Appias albina darada, Artogeia erutae montana, Miletus mallus, Flos fulgida fulgida, Cigaritis nipalicus, Rapala rectivitta, Heliophorus kohimensis, H. tamu, Jamides caeruleus, Tarucus venosus, Everes huegelii dipora, Talicada nyseus nyseus, Lestranicus transpectus, Euploea radamanthus radamanthus, Lethe distans, L. dura gammiei, L. latiaris latiaris, L. sura, Neope pulaha, N. yama yama, Zipaetis scylax, Algia fasciata fasciata, Athyma opaline, Pantoporia paraka paraka, Kallima knyvettii, Celaenorrhinus asmara, Hyarotis adrastus praba, Erionota torus, Baoris penicillata chapmani, and Potanthus mingo ajax of which, Miletus mallus was a new record for India. Ninety species are legally protected in schedules (I, II & IV) of Indian (Wildlife) Protection Act, 1972.